Formulation of a sustainable medium for the direct lactic acid fermentation of sago starch using Enterococcus faecium DMF78 - Tan, Adeline Go (2010)
Direct L(+)-lactic acid fermentation from starch is only possible with a few novel microorganisms, one of which is the amylolytic homofermentative Enterococcus faecuim DMF78 which uses sago as substance.